The effect of providing a variety of food menus on increasing toddler weight at preschool harapan bangsa north labuhan batu regency in 2020 - Herna Rinayanti Manurung (Institute of Computer Science (IOCS), 2022)
Media Leaflets are an idea that goes straight to the point and describes how to take action in a short and concise manner. Leaflets are very effective in conveying short and concise messages. like posters, they are also easy to carry and distribute. Even because of the compact size, the amount carried can be more than the poster. This kind of study is called a quasi-experimental (quasi-experiment), in which experimental activities are carried out with the goal of identifying a symptom that develops as a consequence of a certain treatment or experiment. A group pre-test and post-test design strategy was used in this study. All participants in this study were toddlers at Harapan Bangsa PAUD, North Labuhanbatu Regency in 2020. totaling 20 PAUD toddlers. The number of samples used was 20 PAUD toddlers obtained by using non-probablity sampling technique, namely by purposive sampling (one of the non-random sampling techniques). The data analysis technique used simple paired t-test. The results of the univariate analysis showed that the provision of media was low regarding dietary variations and low toddler weight. The results of the Bivariate analysis showed that there was an effect of giving food variety media on the weight gain of toddlers in PAUD Harapan Bangsa, Labuhanbatu Utara Regency in 2020. There is an effect of giving food variety leaflets on the weight gain of toddlers in Harapan Bangsa PAUD, North Labuhanbatu district in 2020.